An embeddable spherical smart aggregate for monitoring concrete hydration in very early age based on electromechanical impedance method. (March 2021) - Fan, Shuli; Zhao, Shaoyu; Kong, Qingzhao; Song, Gangbing
In this paper, a new embeddable spherical smart aggregate (SSA) was utilized to monitor concrete curing in very early age. Overcoming the limitation of the existing PZT-patch-based transducers, the SSA provides vital changing information in all directions of host structure. To verify the advantage of SSA in structural health monitoring (SHM), the sensitivities of SSA and smart aggregate (SA) in monitoring concrete cube deformation and stiffness variation were analyzed and compared by numerical simulation. The feasibility of SSA in monitoring the concrete hydration process was studied by experiments utilizing electromechanical impedance (EMI) technique. At last, four SSAs were embedded in a concrete column to study the practicality of SSA in monitoring the concrete curing process in very early age. The EMI signatures and the root mean square deviation (RMSD) values of the collected information from SSAs were analyzed. The results illustrate that the SSA is more sensitive than SA in monitoring the concrete deformation and stiffness variation. The data measured by SSA in monitoring the concrete hydration process fluctuates more obviously than the data recorded by SA. The new spherical transducer can effectively and reliably monitor the concrete hydration process.